Electronic Raman scattering through a stripe ordering transition in La2-xSrxNiO4: Магнетизм - Gnezdilov, V. P.; Pashkevich, Yu. G.; Yeremenko, A. V.; Lemmens, P.; Güntherodt, G.; Tranquada, J. M.; Buttrey, D. J.; Nakajima, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We describe the results of electronic Raman scattering experiments in two differently doped single crystals of La2-xSrx NiO4 (x = 0.225 and 1/3). In B1g symmetry a crossover from weakly interacting to pseudogap-like behavior is observed at a charge-ordering temperature Tco. In B2g symmetry a redistribution of electronic continua with decreasing temperature is accompanied by a loss of spectral weight below Tco in the low-frequency region due to opening of a pseudogap. The slope of the Raman response at vanishing frequencies is investigated, too. Its temperature behavior in B2g symmetry, which predominantly selects charge carriers with momenta along the diagonals of the NiO2 bonds, provides clear evidence for one-dimensional charge transport in the charge-ordered phase.